Instituições culturais-cognitivas e a inovação em uma universidade pública brasileira - Gallon, Ives (2019)
Institutional theory has contributed significantly to organizational studies by allowing the understanding of phenomena that affect organizational efficiency beyond those related to resource rationalization and technological imperatives. The existence of institutional forces that affect the efficiency of organizational structures has been perceived, making them yield to cultural elements, in search of legitimacy before the social environment. In the educational sector, these institutionalized norms are preponderant in determining structures and processes, unlike in other economic sectors. Thus, federal higher education institutions are organizations that are conducive to the development of institutional studies. Its structures are extremely complex, due to the diversity of its publics, developed activities, manipulated technologies, the diverse training of the people involved and the extension of its infrastructure. And, along with this, universities are considered spaces to innovation, considering the multiplicity of knowledge produced and disseminated in this scope. This study aimed to analyze cultural-cognitive institutions that promote or inhibit innovation in a Brazilian public university. The first stage of the work focused on identifying the cultural-cognitive elements as well as the manifestations of these elements in university culture that could promote or inhibit innovation. Based on this investigation, the instrument of data collection was elaborated and, later, submitted to the validation of specialists. In the second stage, a survey was carried out with university professors, taking into account their relevance in scientific production. The research was applied during the months of August and October 2018, obtaining 324 responses from a total of 1820 teachers. The data of the research were analyzed through descriptive statistics and non-parametric tests of difference of averages, crossing the cultural-cognitive elements with the variables of the professor’s profile. In the descriptive analysis, eighteen cultural-cognitive manifestations promoting innovation and six inhibiting were confirmed. In addition, sixteen cultural-cognitive manifestations inhibiting innovation and twenty-eight cultural-cognitive manifestations promoting innovation were not confirmed. In the difference of averages analysis, different perceptions of the respondents of the research were identified in relation to the cultural-cognitive manifestations, based on the profile variables. The variables gender, participation in innovation projects with the private sector, participation in innovation projects focused on the internal activities of the institution and educational center stand out. Thus, it can be seen that the cultural institutions that promote and inhibit innovation are not homogeneously perceived within the university, and can generate different organizational results in terms of innovation.